2016
DOI: 10.2147/dddt.s120014
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of cisplatin on the severity of testicular injury in Sprague Dawley rats: reactive oxygen species and endoplasmic reticulum stress

Abstract: Cisplatin (CIS) is used in the treatment of cancer, but its nonspecific systemic actions lead to toxic effects on other parts of the body. This study investigated the severity of CIS toxicity by increasing its dose over a constant time period. Sprague Dawley rats were divided into five treatment groups and control group with CIS (2, 4, 6, 8, and 10 mg/kg) administered intraperitoneally for 5 days. The body and organs were weighed, epididymal sperm was counted, and sperm motility and sperm apoptosis were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 32 publications
(29 reference statements)
7
54
0
Order By: Relevance
“…caspase-12, a marker of apoptosis, is localized on the ER and is specifically activated via erS, and not via membrane or mitochondrial signals. it has been reported that erS-mediated apoptosis is important in cP-induced nephrotoxicity, suggesting that er is a target of cP, and that GrP78, caspase-12 and cHoP are important molecules (9,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…caspase-12, a marker of apoptosis, is localized on the ER and is specifically activated via erS, and not via membrane or mitochondrial signals. it has been reported that erS-mediated apoptosis is important in cP-induced nephrotoxicity, suggesting that er is a target of cP, and that GrP78, caspase-12 and cHoP are important molecules (9,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a single dose of cisplatin induced a substantial weight loss of 8% of body weight by day 5, and 16% by day 10 (compared to 10% weight gain in controls at day 10). This general toxicity of cisplatin in rats is recognised (Ilbey, Ozbek, Cekmen, et al., ; Ilbey, Ozbek, Simsek, et al., ; Soni et al., ), and has been shown to be linearly dependent on cisplatin dose (Soni et al., ). Weight loss, largely due to anorexia, affects 50%–90% of patients receiving cisplatin (Hesketh, ), and is a debilitating problem for patients who are unable to maintain adequate nutrition, contributing to reduced quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cells that produce testosterone are suggested to be susceptible to ROS damage (Soni et al, 2016) (Fathabad, Shekarforoush, Hoseini, & Ebrahimi, 2018;Morakinyo, Achema, & Adegoke, 2010). It is thus conceivable that the restoration of the sex hormones could be mediated by the action of ginger juice compounds on Leydig cells and hypothalamic-pituitary axis.…”
Section: F I G U R Ementioning
confidence: 99%